Higher detectability of amyloid with phenol Congo red compared with alkaline Congo red - Marta Legatowicz-Koprowska; Justyna Szczygieł; Małgorzata Mańczak; Ewa Walczak (Rheumatology)
Introduction Amyloidosis is a heterogeneous group of conditions associated with tissue deposition of insoluble abnormal proteins that damage vital organs. Early diagnosis, when the deposits are minimal, determines the prognosis and requires histological confirmation. The commonly adopted gold standard technique is alkaline Congo red (ACR) staining, though its sensitivity is limited. There is a need for a simple and inexpensive screening method offering a better chance of detecting minimal amyloid deposits. The aim of this study was to compare amyloid detectability with ACR and phenol Congo red (PHCR) staining techniques for early detection of minimal deposits.